All-solid-state polymeric screen printed and carbon paste ion selective electrodes for determination of oxymetazoline in pharmaceutical dosage forms - Rizk, Mohamed Salem; Hussien, Emad Mohamed; El-Eryan, Rasha Tharwat; Daoud, Amira Mohamed (European Journal of Chemistry, 2019)
All-solid state potentiometric ion selective electrodes have the merits of being portable, small and suitable for small volume samples. Herein, disposable home-made screen printed polymeric ion selective electrode (SPE) is developed for determination of oxymetazoline (OXM) in pharmaceutical nasal drops and drug substance. Ion selective electrodes with optimal potentiometric response were achieved by careful selection of the ion exchanger and plasticizer. A screen printed electrode utilizing oxymetazoline-tetraphenyl borate (OXM-TPB) as an ion exchanger and dibutyl phthalate (DBP) as a plasticizer exhibited a Nernstian slope of 59.5±0.5 mV/decade (n=3) over the concentration range from 1×10-5 to 1×10-2 M OXM (r = 0.9999) with a detection limit of 5.0×10-6 M. The electrode is useful over a wide pH range from 4.0 to 8.0. The electrode showed a high selectivity for OXM against several common interfering ions. The potential interference from benzalkonium chloride was easily eliminated by treatment the sample with KI. Comparable potentiometric characteristics including linearity, detection limit, pH range and selectivity pattern were obtained with a carbon paste electrode (CPE) comprising same ion exchanger and plasticizer. The electrodes were successfully used for the assay of OXM in the drug substance and in the dosage form in presence of benzalkonium chloride with high accuracy (±2%) and precision (%RSD ˂2.5). The proposed method is simple, accurate and precise.